"Every part of me has changed"—shared lived experiences of adolescents living with cancer in Zambia. Issue 1 (March 2019) - Sibulwa, Sharleen; Chansa-Kabali, Tamara; Hapunda, Given
This study explored experiences of adolescents living with cancer, focusing on physical and psychosocial problems. Semi-structured interviews were carried out on 18 adolescents aged between 12 and 18 years. Transcripts were analyzed using thematic analysis. Results showed that the adolescents faced a lot of physical, psychological, and social problems due to cancer diagnosis, treatment, and care. In order to improve their well-being and quality of life, psychosocial interventions should be incorporated in biomedical interventions that adolescents with cancer receive. This study proposes cost-effective interventions that can be implemented in resource-restricted sub-Saharan countries like Zambia.